Role of Triglyceride-Glucose Index in Type 2 Diabetes Mellitus and Its Complications - Pan Y; Zhao M; Song T; Tang J; Kuang M; Liu H; Zhong S (Diabetes, Metabolic Syndrome and Obesity, 2024)
Ying Pan,1 Mengjie Zhao,1 Tiantian Song,2 Jia Tang,2 Ming Kuang,2 Hongying Liu,2,* Shao Zhong3,* 1Department of General Practice, Kunshan Hospital Affiliated to Jiangsu University, Kunshan, Jiangsu, People’s Republic of China; 2Hangzhou Kang Ming Information Technology Co., Ltd, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Endocrinology, Gusu School, Nanjing Medical University, The First People’s Hospital of Kunshan, Kunshan, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shao Zhong, Department of Endocrinology, Gusu School, Nanjing Medical University, the First People’s Hospital of Kunshan, Kunshan, 215300, People’s Republic of China, Tel +86 13328056828, Email drzhong@163.com Hongying Liu, Hangzhou Kang Ming Information Technology Co., Ltd, Hangzhou, 310000, People’s Republic of China, Tel +86 02164045531, Email hongyingliu@91jkys.comAbstract: Insulin resistance (IR) is the major mechanism in the pathogenesis of type 2 diabetes mellitus (T2DM). Early identification of IR is of great significance for preventing the onset of T2DM and delaying the progression of the disease. Previous studies have shown that triglyceride-glucose (TyG) index can be used as an effective surrogate marker for IR. There is a significant correlation between TyG index and T2DM and its common complications. In addition, the predictive efficacy of TyG index is better than that of other IR surrogate indicators. TyG index may not only become an important marker to identify people at high risk of T2DM and its complications, but is also expected to become a strong predictor of the prognosis of these diseases. However, there are still some challenges in the widespread application of TyG index in clinical practice. In the future, more high-quality studies are needed to clarify the assessment methods of TyG index for the prognosis of T2DM and its complications. Further investigations of the relationship between TyG index and T2DM and its complications will be expected to provide new ideas and methods for the prevention and treatment of T2DM and its complications.Keywords: triglyceride-glucose index, type 2 diabetes mellitus, complication, insulin resistance